TRIM32, but not its muscular dystrophy-associated mutant, positively regulates and is targeted to autophagic degradation by p62/SQSTM1 - Overå, Katrine Stange (J Cell Sci, 2019)
The tripartite motif (TRIM) proteins constitute a family of ubiquitin E3 ligases involved in a multitude of cellular processes, including protein homeostasis and autophagy. TRIM32 is characterized by six protein–protein interaction domains termed NHL, various point mutations in which are associated with limb-girdle-muscular dystrophy 2H (LGMD2H). Here, we show that TRIM32 is an autophagy substrate. Lysosomal degradation of TRIM32 was dependent on ATG7 and blocked by knockout of the five autophagy receptors p62 (also known as SQSTM1), NBR1, NDP52 (also known as CALCOCO2), TAX1BP1 and OPTN, pointing towards degradation by selective autophagy. p62 directed TRIM32 to lysosomal degradation, while TRIM32 mono-ubiquitylated p62 on lysine residues involved in regulation of p62 activity. Loss of TRIM32 impaired p62 sequestration, while reintroduction of TRIM32 facilitated p62 dot formation and its autophagic degradation. A TRIM32(LGMD2H) disease mutant was unable to undergo autophagic degradation and to mono-ubiquitylate p62, and its reintroduction into the TRIM32-knockout cells did not affect p62 dot formation. In light of the important roles of autophagy and p62 in muscle cell proteostasis, our results point towards impaired TRIM32-mediated regulation of p62 activity as a pathological mechanisms in LGMD2H.